Pelatihan Pembuatan Pupuk Organik Cair Dan Kompos Berbahan Dasar Sampah Organik Pasar Pada Ibu-Ibu Rumah Tangga Di Desa Sungai Kakap Kabupaten Kubu Raya Kalimantan Barat - Mukarlina, Mukarlina; Khotimah, Siti; Zakiah, Zulfa; Turnip, Masnur; Rahmawati, Rahmawati; Saputra, Firman (Future Science, 2023)
Activities carried out by housewives in Sungai Kakap village include cultivating their yards by planting horticultural plants (vegetables and fruit). The obstacle in increasing the yield of garden plants is the high cost of non-organic fertilizers. However, until now the people in the village do not know the source of organic waste that can be used as fertilizer, namely plant-based organic waste that comes from the market. This training aims to provide knowledge and skills to housewives regarding organic fertilizer and increase the knowledge and skills of housewives in making organic fertilizer from plant-based market waste. The service program is carried out by conveying the theory of organic fertilizer and the practice of making compost and liquid organic fertilizer (POC) from market organic waste made from fruit and vegetables. Evaluation of community service activities is carried out using a questionnaire method given at the beginning and end of the activity. The results of the questionnaire showed an increase in the knowledge of housewives in Sungai Kakap Village about organic fertilizer (100%), an increase in interest in applying organic fertilizer (97%), and an increase in interest in making their own organic fertilizer (80%).